ORGAN DONATION AND TRANSPLANTATION IN RUSSIAN FEDERATION IN 2011 - S. V. Gautier; Y. G. Moysyuk; S. M. Khomyakov; O. S. Ibragimova (Вестник трансплантологии и искусственных органов)
Registry data analysis shows stabilization of indicators of donor and transplant activity in 2011 after continuous growth within five years, increase in a share of effective donors after brain death and multi-organ explantation, development of thoracic organs transplantation and living related donor kidney transplantation. In the conditions of decentralization of organ donation and transplant programs it is necessary to develop coope- ration between transplant centers and to expand the practice of an interregional exchange of donor organs. The federal law «About bases of health protection of citizens in the Russian Federation», accepted in 2011, creates a legal basis for development and acceptance of the new legislation in the sphere of organ donation and transplantation.